Erratum - Editorial Staff (University of Kansas Libraries, 2009)
Bradly David Ridpath, first author of the article "Changing Sides: The Failure of the Wrestling Community's Challenges to Title IX and New Strategies for Saving NCAA Sport Teams" in JIS Volume 1 Issue 2, should have been identified as Co-founder, Legal Institute for Gender Equity in Athletics. The Journal of Intercollegiate Sport regrets the error.